Protein expression upon desiccation and imbibition of Magnolia ovata A. St.-Hil seeds - José, Anderson Cleiton; Silva, Edvaldo Aparecido Amaral da [UNESP][; Davide, Antonio Claudio; Toorop, Peter (Brazilian Archives of Biology and Technology, 2011)
The effect of seed drying and imbibition was studied by differential protein expression using two dimensional gel electrophoresis. After drying to a range of water contents, seeds were germinated to assess the viability. Seeds of Magnolia ovata did not withstand the desiccation down to 0.10 g H2O · g-1 dw. The critical water content below which the desiccation sensitivity became apparent was around 0.18 g H2O · g-1 dw (-26.5 MPa). Total protein was extracted and separated by 2D electrophoresis from fresh seeds (0.28 g H2O · g-1 dw), mild dried seeds (0.25 g H2O · g-1 dw) and seeds at low water content (0.10 g H2O · g-1 dw) before and after imbibition for 10 days. The proteome profile revealed the presence of 588 spots on each silver stained gel, from which 21 showed differential expression, correlated with desiccation and germination, by increased or decreased expression. After MS/MS sequencing, three protein spots produced spectra that matched to a Magnolia salicifolia legumin precursor. Results suggested an involvement of this protein in the events taking place during the drying and subsequent imbibitions of the dried seeds.
Keywords: desiccation tolerance; forest seed; legumin; proteomics